2018
DOI: 10.1159/000486696
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepines as a Monotherapy in Depressive Disorders: A Systematic Review

Abstract: Background: The aim of this paper was to perform a systematic review and, when feasible, a meta-analysis of randomized controlled trials (RCT) which used benzodiazepines (BZD) as a monotherapy versus placebo, antidepressant drugs (AD), or both. Methods: Keyword searches were conducted for identifying RCT comparing BZD and AD, and/or placebo in the treatment of depression, using electronic databases from their inception up to April 2017. We selected reports of RCT in which BZD were compared to AD and/or placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 61 publications
1
23
0
3
Order By: Relevance
“…Actually, Bushnell and colleagues showed, in a large sample of 765 depressed patients, no significant clinical differences in continuation of antidepressant treatment between simultaneous administration of BZDs plus antidepressant and antidepressant alone (Bushnell et al, ; Rizvi, Sproule, Gallaugher, McIntyre, & Kennedy, ). It needs also to be taken into account that, contrary to guidelines recommendations, a recent review found no significant differences in acute treatment response (up to 12 weeks) between BZDs and tricyclic antidepressants in patients with depressive disorders (Benasi et al, ). Nonetheless, it is important to stress that mood disorders often exhibit a chronic course with multiple episodes, making the choice of treatment particularly relevant beyond the short‐term.…”
Section: Discussionmentioning
confidence: 96%
“…Actually, Bushnell and colleagues showed, in a large sample of 765 depressed patients, no significant clinical differences in continuation of antidepressant treatment between simultaneous administration of BZDs plus antidepressant and antidepressant alone (Bushnell et al, ; Rizvi, Sproule, Gallaugher, McIntyre, & Kennedy, ). It needs also to be taken into account that, contrary to guidelines recommendations, a recent review found no significant differences in acute treatment response (up to 12 weeks) between BZDs and tricyclic antidepressants in patients with depressive disorders (Benasi et al, ). Nonetheless, it is important to stress that mood disorders often exhibit a chronic course with multiple episodes, making the choice of treatment particularly relevant beyond the short‐term.…”
Section: Discussionmentioning
confidence: 96%
“…Benzodiazepines and related drugs (BZRDs) are commonly used to treat diverse psychiatric disorders, including depression, anxiety, insomnia, and panic attacks . These drugs are frequently prescribed in clinical practice for the general population, and the prevalence of BZRD use among the elderly is as high as 40% .…”
Section: Introductionmentioning
confidence: 99%
“…In elderly subjects in Japan, those with sleep-onset insomnia were more likely to experience depression 3 years later [28]. Benzodiazepines are often used concomitantly with antidepressants to treat anxiety, and have been reported to be as effective as monotherapy in the treatment of anxious depression [29]. As sleep-onset insomnia often correlates with anxiety, anxiolytic benzodiazepines may potentially shorten sleep latency.…”
Section: Discussionmentioning
confidence: 99%